Development and Survivorship of Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) on Local Rice Varieties from West Sumatra, Indonesia - Jufia, Humaira; Hidrayani, Hidrayani; Nelly, Novri (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2025)
Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae), or the fall armyworm (FAW), is an invasive and highly polyphagous pest that threatens various food crops, including rice. This study aimed to assess the effects of several local rice cultivars from West Sumatra on the development and survival of S. frugiperda under laboratory conditions. The experiment was arranged in a completely randomized design with five treatments and ten replications. Four local rice cultivars (Cisokan, Batang Piaman, Kuriak Kusuik, and Bujang Marantau) were tested, with corn used as a reference host. Data were analyzed using analysis of variance (ANOVA). The observed parameters included the duration of each developmental stage, as well as the pre-oviposition, oviposition, and post-oviposition periods, fecundity, egg hatchability, larval survival to the pupal stage, pupal weight, adult emergence, and sex ratio. Host plant species significantly affected all developmental and reproductive parameters of S. frugiperda (p < 0.05). The total developmental duration was shorter on corn (37.20 ± 1.51 days) than on the local rice cultivars, which ranged from 41.54 to 41.90 days. The larval stage lasted longer on rice cultivars (mean 21.40 days) compared with corn (15.86 days). Female longevity and oviposition period were also greater on corn than on rice. Overall survival and the number of females emerging were lower on rice (73.20–78.80 individuals) than on corn (94.20 individuals). These results indicate that S. frugiperda is capable of completing its life cycle on local rice cultivars; however, development is slower, and reproductive potential is reduced compared to corn.